Nilai Perusahaan Food & Beverage Yang Terdaftar Di Bursa Efek Indonesia Pada Periode 2018-2022 Yang Dipengaruhi Oleh Rasio Profitabilitas, Rasio Aktivitas, Dan Rasio Leverage - Dimas Akendy; Kumba Digdowiseiso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of Return On Assets, Curret Ratio, Debt to Asset Ratio on Price Book Value. The population in this study are Food & Beverage companies listed on the Indonesia Stock Exchange. Sampling in this study used a purposive sampling technique in order to obtain a sample of 26 with each period of 5 years. The data that can be obtained in this study is 130 data resulting from the number of samples multiplied by the period. The analytical method of this study uses panel data regression with the STATA Statistics application version 17. Partially, the results of this study indicate that Return On Assets has a negative and significant effect on Price Book Value. Current Ratio has a negative and significant effect on Price Book Value, and Debt to Asset Ratio has a positive but not significant effect on Price Book Value. Simultaneously Return On Assets, Current Ratio, and Debt to Asset Ratio have a significant effect on Price Book Value. Keywords: Return On Assets;Current Ratio;Debt to Asset Ratio;Price Book Value